PERSEPSI MAHASISWA TERHADAP PEMANFAATAN ZOOM MEETING DAN WHATSAPP DALAM PEMBELAJARAN MENULIS ARTIKEL ILMIAH POPULER DI MASA PANDEMI - Ari Suryawati Secio Chaesar; Titi Setiyoningsih (BAHAS, 2022)
Abstract  The purposes of this study was to determine student perceptions of the use of zoom meetings and whatsapp in leaning to write popular scientific aticles during the pandemic. This study uses qualitative descriptive research method which aims to describe the analysis of the results of questionnaires, interviews, and literature studies. The subject and objects in the study were Sebelas Maret University stundets as many as 121 respondent in semesters I and III who had the status of taking Indonesian General Courses online in odd semesters. Data collection techniques were carried out by distributing online questionnaires, interviews, and literature studies. The results showed that the zoom meeting dan whatsapp applications can provide convenience in online learning (52,1% agree), make it easier for students to understand learning (65,3% agree), learning is more flexible (64,5% agree), the use of applications make learning complicated (70,2% disagree), students become more confident (66,1% agree), it is easy for students to consult related to assignments with lecturers (62% agree), high learning motivation (72,7% agree), relevant to use in learning to write scientifict articles during the pandemic (66,9% agree), increasing creativity (70,2 agree), respond to questions and ions in learning (57% strongly agree), effectively used in learning to write populer scientific articles (62% agree), become a learning solution during a pandemic (66,1% agree) lecturer and stundent interactions student become more familiar (57 agree), and value obtained will increase (57,9% agree). It can be concluded that the use of zoom meetings and whatsapp in leaning to write popular scientific articles gets a good perception from students and lecturers are advised to always motivate students to take part in online learning. Keywords: Perception, Zoom Meeting, WhatsApp, Writing Learning, Popular Article